Ecbasis Cuiusdam Captivi Per Tropologiam-Escape of a Certain Captive Told in a Figurative Manner An Eleventh-Century Latin Beast Epic - Zeydel, Edwin H., 1893-1973; Project Muse; Project Muse. (Project Muse, 2020)
The oldest medieval beast epic was translated literally into English prose for the first time in this volume, with Latin on facing pages. The introduction and commentary by Zeydel familiarize the reader with the history and value of the text and constituted a new approach, arguing for the inclusion of Latin literature composed in what is now Germany in the history of German literature.
Issued as part of book collections on Project MUSE.
Includes bibliographical references (pages 18-20).
Description based on print version record.
Keywords: Latin poetry, Medieval and modern -- Translations into English; Latin poetry, Medieval and modern; Electronic books; Centos; Electronic books